Facebook Group in Writing Activities: Students’ Voices - Solihin, Aminus; Hasanah, Amalia; Desvitasari, Deta (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
This study was aimed to find out students’ perceptions on the use of Facebook group in writing activities. The design of this study was a qualitative research with a case study. This study was conducted at one of senior high schools in Palembang, with two eleventh-grade students of natural science class and two students of social science class by using maximum variation sampling technique. In collecting data, one-on-one interview with open-ended questions through phone was used in this study. The data were analyzed by using thematic analysis in the form of codes and themes. The findings of the study demonstrated that students perceived the use of Facebook in writing activities brought both benefits and drawbacks. The benefits were (1) Facebook group assisted the students in the process of writing in terms of planning, drafting, and final version, (2) Facebook group facilitated the students to practice the component of writing in terms of organization, content, spelling, vocabulary, and grammar, (3) Facebook group encouraged students’ participation, (4) Facebook group boosted students’ motivation and confidence to write, and (5) Facebook group was easy to access because of steady internet connection. Nevertheless, the drawbacks of the Facebook group in writing activities as perceived by the students covered (1) Facebook group did not promote the editing process of writing, (2) Facebook group did not assist the students in using capitalization and punctuation, (3) the students got distracted by other features of Facebook, and (4) the students received slow feedbacks for their writing from the teacher and classmates.